Microbial diversity, morpho-textural characterization, and volatilome profile of the Portuguese thistle-curdled cheese Queijo da Beira Baixa PDO. (July 2022) - Cardinali, Federica; Foligni, Roberta; Ferrocino, Ilario; Harasym, Joanna; Orkusz, Agnieszka; Franciosa, Irene; Milanović, Vesna; Garofalo, Cristiana; Mannozzi, Cinzia; Mozzon, Massimo; Cocolin, Luca; Osimani, Andrea; et al.
Graphical abstract: Highlights: Microbiota and volatile compounds in Queijo da Beira Baixa PDO cheese were studied. Lacotococcus lactis was present at high relative frequency in all the samples. Loigolactobacillus coryniformis and Lactococcus piscium were also detected. Mycobiota showed high prevalence of Candida sake and Starmerella spp. Carboxylic acids, esters, carbonyl compounds, and alcohols were the main VOCs. Abstract: The aim of the present study was to characterize the bacterial and fungal communities naturally occurring in Queijo da Beira Baixa PDO cheese samples produced in Castelo Branco district (Beira Baixa Region, Portugal) through viable counts and metataxonomic analyses. Physico-chemical and morpho-textural analyses were also carried out, together with the analysis of volatile organic compounds (VOCs). In the analyzed samples, pH values ranged between 4.72 ± 0.15 and 5.85 ± 0.02, with values of lactic acid content comprised between 0.64 ± 0.00 and 1.95 ± 0.16 g 100 g −1 . Specific volume of cheese ranged from 1.09 ± 0.08 to 1.32 ± 0.02 g mL −1 . Texture profile analysis showed hardness ranging between 38.3 ± 9.6 N and 68.55 ± 7.5 N. As for lactic acid bacteria, presumptive lactococci, thermophilic cocci, and lactobacilli counts up to 9 Log cfu g −1 . Coagulase-negative cocci showed counts up to 7 Log cfu g −1 . Enterococci counts were up to 6 Log cfu g −1 . Finally, counts of eumycetes showed values up to 4 Log cfu g −1 . The results of metataxonomic analysis of bacteria showed the dominance of Lactococcus lactis in all the samples. Moreover, other taxa were detected, including Lactiplantibacillus plantarum, Loigolactobacillus coryniformis, Lactococcus piscium, Streptococcus thermophilus, and Lacticaseibacillus zeae . Mycobiota was characterized by the presence of Candida sake, Ustilago, Cladosporium variabile, Starmerella, Debaryomyces hansenii, and Pichia kluyveri . In the analyzed Queijo da Beira Baixa PDO cheese samples, carboxylic acids represented the most detected VOCs, followed by esters, carbonyl compounds, and alcohols.